Análise dos aspectos éticos da pesquisa em seres humanos contidos nas Instruções aos Autores de 139 revistas científicas brasileiras - Sardenberg, Trajano [UNESP]; Müller, Sérgio Swain [UNESP]; Pereira, Hamilton da Rosa [UNESP]; Oliveira, R. A. de [UNESP]; Hossne, W. S. [UNESP] (Associação Médica Brasileira, 1999)
OBJETIVO: Estudar as normas relativas à ética da pesquisa em seres humanos contidas nas Instruções aos Autores de revistas científicas brasileiras. MATERIAL E MÉTODOS: As Instruções aos Autores de 139 revistas científicas brasileiras das áreas de medicina, biomedicina, enfermagem, odontologia e ciências gerais foram analisadas com relação às suas recomendações sobre os aspectos éticos. RESULTADOS: Das 139 revistas estudadas, 110 (79,1%) não fazem referências aos aspectos éticos; 17 (12,2%) exigem aprovação prévia pela Comissão de Ética; três (2,1%) fazem referência à Declaração de Helsinque; uma (0,7%) recomenda adotar o consentimento esclarecido; cinco (3,5%) seguem orientações dos requisitos uniformes para manuscritos submetidos a revistas biomédicas e três (2,1%) seguem princípios, normas e padrões éticos não especificados. Nas 29 revistas que fazem referências à ética, as exigências são solicitadas sob as seguintes formas: 15 (51,7%) exigem a inclusão da informação no texto do artigo; duas (6,8%) pedem carta assinada pelos autores; uma (3,4%) solicita cópia da autorização da Comissão de Ética; uma (3,4%) afirma supor que o autor cumpriu as exigências e dez (34,4%) não fazem qualquer referência específica. CONCLUSÕES: Os resultados do estudo indicam que na maioria das revistas científicas brasileiras há pouca preocupação em relação aos aspectos éticos da pesquisa em seres humanos, contidas nas Instruções aos Autores. Nas revistas que fazem referência aos aspectos éticos, as exigências são muito variáveis.

The concern with ethical standards during research in human subjects has been improving in Brazil during the last decade. Analysis of the ethical recommendations in instructions to authors may contribute to understand Brazilian Scientific Journals policies. OBJECTIVE: to evaluate the recommendations related to the ethics of investigation in human subjects in instructions to authors of Brazilian Scientific Journals. MATERIAL and METHODS: instructions to authors of 139 Brazilian Scientific Journals in medicine, biomedicine, nursery, odontology and general sciences were analysed. RESULTS: ln one hundred ten (79.1%) of the 139 journals no recommendations related to ethics were found; 17 (12.2%) required previous approval by the institutional committee; 3 (2,1 %) the procedures should be in accordance with the Declaration of Helsinki; 1 (0.7%) recommends the aplication of the informed consent; 5 (3.5%) recommend the use of Uniform requeriments for manuscripts submitted to biomedical journals and 3 (2.1%) follow no specified rules. Twenty nine journals ask for references in ethics standards: in 15 (51.7%) the information must be included in the text; in 2 (6,8%) the authors must send a letter informing how the ethics standards were followed; in 1 (3.4%) a copy of the approval by the institutional committee must be included; in 1 (3,4%) believed the authors followed the standards and in 10 (34.4%) no specific reference was made. CONCLUSION: these results indicated that the majority of Brazilian Scientific Journals have little concern related to ethical aspects of research in human subjects included in instructions to authors. Even journals that make references to the ethical aspects the recommendations are quite different.
Recommendations on ethical aspects included in the instructions to authors: analysis of 139 Brazilian Scientific Journals
Keywords: Ética; Bioética; Pesquisa; Editoração; Periódicos; Ethics; Bioethics; Research; Editoring; Journals